Effect of real-world fear on risky decision-making in medical school-based students: A quasi-experimental study - Wang, Lei; Chen, Sheng; Xiao, Wei (Frontiers in behavioral neuroscience, 2023)
Objective: To explore the effect of real-world fear on risky decision-making under certainty and uncertainty. Methods: This quasi-experimental study enrolled non-psychology undergraduate volunteers aged between 17 and 20 years old from the Preventive Medical Institute medical school in Xi’an. Participants were randomly divided into two groups, and each group received a two-stage crossover design intervention (of a calm and fearful situation) and completed the tasks of risky decision-making under uncertainty (the balloon analog risk task: BART) and certainty (the Cambridge gambling task: CGT), respectively. The primary outcomes included the behavioral impulsivity measured by the BART value, and the speed of decision-making, the quality of decisions, the adventure index, behavioral impulsivity, and risk adjustment measured by CGT. The secondary outcome was the concentration of cortisol in the saliva. Results: A total of 60 questionnaires and data were obtained from 60 participants (28 males and 32 females, aged 19.55 ± 0.75). Compared with the calm situation, participants were more likely to have a lower BART value ( p = 0.013), slower speed of decision-making ( p < 0.05), and higher adventure index ( p = 0.018) in the fearful situation. The quality of decisions ( p = 0.189), behavioral impulsivity index ( p = 0.182), and risk adjustment ( p = 0.063) between subjects in the fearful and calm situations were comparable. Furthermore, the mean value of the adventure index of CGT in male subjects was significantly higher than that in female subjects ( p < 0.05), and the cortisol concentration in saliva during the fearful situation was significantly higher compared to the calm situation ( p < 0.05). Conclusion: Fear might reduce behavioral impulsivity under uncertainty, and increase the adventure index under certainty in risky decision-making. Risky behavior might be influenced by gender: under certainty in risky decision-making, men were more adventurous. Additionally, fear increased the secretion of cortisol in saliva.